First scattered light detection of a nearly edge-on transition disk around the T Tauri star RY Lupi - Langlois, Maud; Pohl, Adriana (Astronomy and astrophysics, 2018)
Transition disks are considered sites of ongoing planet formation, and their dust and gas distributions could be signposts of embedded planets. The transition disk around the T Tauri star RY Lup has an inner dust cavity and displays a strong silicate emission feature. Using high-resolution imaging we study the disk geometry, including non-axisymmetric features, and its surface dust grain, to gain a better understanding of the disk evolutionary process. Moreover, we search for companion candidates, possibly connected to the disk.
Gesehen am 20.04.2020